2015
DOI: 10.1021/acs.chemmater.5b01971
|View full text |Cite
|
Sign up to set email alerts
|

Template Synthesis of CuInS2 Nanocrystals from In2S3 Nanoplates and Their Application as Counter Electrodes in Dye-Sensitized Solar Cells

Abstract: We report the room temperature template synthesis of CuInS 2 nanocrystals through incorporation of Cu + cations into In 2 S 3 nanoplates whose chemical composition has been controlled by varying the amount of copper ions in the reaction mixture. As a result, bandgaps of the resultant CuInS 2 nanoplates can be tuned from 1.45 to 1.19 eV with [Cu]/[In] molar ratios increasing from 0.7 to 2.9, which was demonstrated by the cyclic voltammetry. We explored the use of CuInS 2 nanocrystals as potential counter electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 75 publications
7
97
0
Order By: Relevance
“…TEM indicated that large, wrinkled nanosheets had formed (Fig 4a, Fig S11). It has been shown previously that Cu + intercalation can occur at room temperature yielding CIS nanocrystals from In 2 S 3 nanocrystals, 26 However, the observed pattern was in good agreement with results from Rogach et al, who assigned their CIS product to the chalcopyrite phase. 26 When CuCl, InCl 3 and thiourea were heated together in a single step, small (~2 nm), spherical particles were observed (Fig S13, S14).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…TEM indicated that large, wrinkled nanosheets had formed (Fig 4a, Fig S11). It has been shown previously that Cu + intercalation can occur at room temperature yielding CIS nanocrystals from In 2 S 3 nanocrystals, 26 However, the observed pattern was in good agreement with results from Rogach et al, who assigned their CIS product to the chalcopyrite phase. 26 When CuCl, InCl 3 and thiourea were heated together in a single step, small (~2 nm), spherical particles were observed (Fig S13, S14).…”
Section: Resultssupporting
confidence: 89%
“…30 Rogach et al incorporated Cu + into In 2 S 3 nanoplates, resulting in CIS with tunable band gap that was used as an efficient counter electrode in dye-sensitized solar cells. 26 Bottom-up approaches, in which growth is limited in one or more dimensions, are typically used to prepare nanostructures such as nanowires and nanoparticles. [31][32][33] In contrast, 2D nanostructures can famously be formed via top-down approaches, such as the separation of 4 graphene and MoS 2 sheets through mechanical or chemical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the af nity of thiol to Cu, CuInS 2 NPs with Cu-rich surfaces are considered energetically favored 12) . Chen et al 21) reported that Cu 3 InS 3 nanocrystals, which contain 3 times as many Cu atoms as In atoms, could take a chalcopyrite structure.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Among of them, the binary transitional-metal sulfides are an attractive family owing to their excellent catalytic activity for I 3 À reduction, the selectivity of transition metals,a nd versatile crystalline morphologies,s uch as WS 2 and MoS 2 . [15] Theextraordinary performance can be traced back to the fascinating morphologies,r ich redox reactions,t unable band-gap structures,a nd diverse photoelectric properties,w hich can be realized by adjusting the component elements and alternating the stoichiometric ratio. [9][10][11] Besides,t he ternary transition-metal sulfides have also been used as the promising CEs and achieved excellent device performances,s uch as NiCo 2 S 4 , [12] MMoS 4 (M = Co,N i), [13] Cu 3 SnS 4 , [14] CuInS 2 .…”
mentioning
confidence: 99%
“…[7,8] Apart from the above-mentioned examples,b inary iron-group transition-metal sulfides,s uch as FeS 2 ,C oS,a nd NiS 2 ,a lso exhibit high catalytic activity for I 3 À reduction. [12][13][14][15][16] As one type of important ternary transition-metal sulfides,t he thiospinels (A II B III 2 X VI 4 ,s uch as CoIn 2 S 4 and NiIn 2 S 4 )have exhibited the viability of photocatalysis and the potential applications in optoelectronics,l ight modulators, and photodetectors. [15] Theextraordinary performance can be traced back to the fascinating morphologies,r ich redox reactions,t unable band-gap structures,a nd diverse photoelectric properties,w hich can be realized by adjusting the component elements and alternating the stoichiometric ratio.…”
mentioning
confidence: 99%